2017
DOI: 10.1002/hed.24679
|View full text |Cite
|
Sign up to set email alerts
|

Treatment‐related determinants of survival in early‐stage (T1–2N0M0) oral cavity cancer: A population‐based study

Abstract: Primary radiation without surgery continues to be used in a subset of early-stage oral cavity SCCs, in which it is associated with decreased OS and DSS. © 2017 Wiley Periodicals, Inc. Head Neck 39: 876-880, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 25 publications
4
54
0
Order By: Relevance
“…On the other hand, dual approaches carry an added level of morbidity and possible compromised wound healing. Furthermore, Sowder et al demonstrated that advanced age and primary SCCHP were factors associated with greater use of nonsurgical approaches . This trend suggests that patient factors involving age and tumor localization to the hard palate may render them poor surgical candidates in whom nonsurgical approaches are ultimately performed …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, dual approaches carry an added level of morbidity and possible compromised wound healing. Furthermore, Sowder et al demonstrated that advanced age and primary SCCHP were factors associated with greater use of nonsurgical approaches . This trend suggests that patient factors involving age and tumor localization to the hard palate may render them poor surgical candidates in whom nonsurgical approaches are ultimately performed …”
Section: Discussionmentioning
confidence: 99%
“…These efforts are primarily guided by attempts to provide evidence‐based data on optimal management of primary subsites and the neck. Primary retromolar trigone (RMT) SCC, though less frequently observed (5.6% vs. 45.2% oral tongue SCC), poses a unique challenge to surgeons, as early mandibular invasion and regional metastases are not uncommon . Factors complicating management are extension to the buccal mucosa, tonsillar pillar, and soft palate …”
Section: Introductionmentioning
confidence: 99%
“…Current management of primary RMT SCC lacks standardization and is mainly guided by the experiences of surgeons as depicted in center‐specific case series. The poorer prognosis of RMT SCC compared with other oral cavity subsites (97.4 vs. 142.2 months, P < .001, overall survival [OS]), and high incidence of local and regional invasiveness necessitates a rigorous evaluation of treatment strategies to enhance patient outcomes . The aim of the current study was to further validate survival outcomes based on treatment modality for patients with RMT SCC using population‐level data.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of HNSCC in certain subsites such as the oropharynx is increasing at a nearly epidemic rate . Unfortunately, appropriate treatment delivery for HNSCC remains a challenge . Tertiary institutions often tailor National Comprehensive Cancer Network (NCCN) guidelines to their specific patient populations through internal algorithms in order to better serve that patient population .…”
Section: Introductionmentioning
confidence: 99%